Structural instability within the active crater of Poás volcano, Costa Rica - Stix, John; Kalacska, Margaret; Arroyo-Mora, Juan Pablo; Lucanus, Oliver; de Moor, J. Maarten; Urquhart, Molly; Campos Vargas, Carlos Andrés (Volcanica, 2025)
This study examines structural patterns in and around the crater of Poás volcano in Costa Rica to determine the current level of stability within the edifice. We used a series of Unoccupied Aerial Vehicle (UAV)-based photogrammetry and thermal infrared surveys to map the active crater, supplemented by satellite imagery to gain a broader view of the regional structural pattern near the volcano. We identified three areas within the eastern crater that exhibit various degrees of instability. The southern sector contains a possible explosion and/or collapse crater; the central zone shows evidence of structural disruption including collapse, fracturing, and/or faulting; and the northern sector contains a new explosion-collapse crater formed in April 2022. Through these three sectors, a principal north–south fault or series of faults truncates the eastern part of the active crater from the rest. These structural patterns continue north and south of the active edifice, demonstrating that east–west extension results in structural weakening at a variety of spatial scales. This weakening is enhanced by rock fracturing caused by volcanotectonic earthquakes and by hydrothermal alteration driven by high-temperature degassing. Because of its instability, the eastern crater area is deserving of further attention from a monitoring and forecasting perspective.